The other Black girl [compact disc, unabridged] : a novel - Harris, Zakiya Dalila (Audioworks, Simon & Schuster Audio, 2021)
Tired of being the only Black employee at Wagner Books, twenty-six-year-old editorial assistant Nella Rogers is thrilled when Harlem-born and bred Hazel is hired until she, after a string of uncomfortable events, is elevated to Office Darling, leaving Nella in the dust.